Receptivity towards Breast Cancer Awareness Materials Message Design and Content - Ting, Su Hie; Ho, Jia-Yiing; Yuwana, Podin (TheShillonga, 2019)
Researchers who studied breast cancer awareness have recommended educational programmes but a major gap in knowledge is whether health promotion materials on breast cancer capture the attention of the audience and educate them on the disease. This case study examined women’s receptivity towards breast cancer leaflets produced by Ministry of Health Malaysia based on the Risk Perception Attitude (RPA) Framework. Five breast cancer brochures were presented to 10 female participants to gauge their receptivity towards the leaflets. The leaflets were analysed for the application of message design principles,notably colour, graphics and typographical features as well as the message content based on RPA constructs.The participants were more receptive towards breast cancer leaflets with susceptibility and self-efficacy messages compared to leaflets with only recommended actions for self-protective behaviour. However, for these behavioural change messages to reach the audience, the message design of the leaflets needs to be thematically linked to known breast cancer campaigns; the pink ribbon and the pink colour. There is a strong non-preference for sketches of woman performing breast self-examination on the leaflets. Considering that susceptibility messages are well-received, inclusion of severity and response efficacy messages could heighten intention to take action. Keywords— breast cancer, health promotion, message design, public receptivity, Risk Perception Attitude framework